Sexual dimorphism in the otolith shape of shi drum, Umbrina cirrosa (L.), in the eastern Mediterranean Sea: Fish size-otolith size relationships - Basusta, Nuri; Durrani, Omerhan (Wiley, 2021)
Little is known about possible differences in sagitta otolith size and shape between sexes of the shi drum, Umbrina cirrosa, and relationships between their body and otolith size. Thus, this study aimed to fill this knowledge gap via examination of 414 sagittal otoliths from 108 male (total length 13.8-26.8 cm) and 99 female (13.5-26.7 cm) U. cirrosa caught between May 2017 and April 2018 in gillnets set at a depth of similar to 15 m in Mersin Bay, Eastern Mediterranean Sea. No statistical differences were observed between the shape indices of the left-sided and right-sided sagitta. However, there were significant differences in the size and shape of otoliths between males and females. The slopes of allometric power functions from otolith width x fish sizes gave significant differences between males and females (ANCOVA, P < 0.05). The relationship for length x weight of otoliths from both males and females showed isometric growth, whereas the relationship of otolith width x otolith weight showed positive allometry. Negative allometric growth was observed for the relationship otolith length x otolith width. In summary, this study revealed the presence of sexual dimorphism in the otolith shape of U. cirrosa, and the data on regression relationships of fish-otolith sizes can be used to estimate fish size from U. cirrosa otolith sizes.
Keywords: Fourier outline; Mersin Bay; morphometric relationships; Sciaenidae; shape descriptors